The interactive effects of turbozyme 160 and diet complexity on starter pig growth performance - M L Lofing; J R Bergstrom; W B Nessmith Jr; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1995)
These results suggest that feeding a complex starter diet improves initial (d 0 to 7 postweaning) growth performance of segregated early-weaned pigs. Feeding either a simple or complex diet with added Turbozyme 160 improves feed efficiency from day 0 to 14 postweaning. However, for the overall experimental period, neither a complex diet nor added Turbozyme 160 had any effect on growth performance.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Starter; Performance; Diet complexity; Enzyme